Bibliometric Analysis on Cryptocurrency: Mapping from 873 Publications - Abdillah; Muhammad (SMART Insight, 2021)
The development of the world economy, especially in Indonesia, cannot be separated from the elements of information technology. The development of information technology will relate to all fields, including the financial sector. Cryptocurrency is a series of cryptographic mechanisms in which there are transaction data and balance sheet data. Cryptocurrency is electronic data so that it does not have a physical form like money in general. There are two ways for someone to get cryptocurrency, namely by mining and/or trading. In Indonesia, most cryptocurrency users currently use their coins for investment, transaction, or payment purposes and remittances, making transfers to different countries. However, along with the increasing interest of the Indonesian people in investing in bitcoin, several obstacles can potentially reduce public interest in cryptocurrencies. This study aims to determine the development of cryptocurrency research trends published by leading journals. The analyzed data consisted of 873 indexed research publications. The data is then processed and analyzed using the VoS viewer application to find out the bibliometric map of cryptocurrency research development.